Synthesis, Chiral Resolution and Enantiomers Absolute Configuration of 4-Nitropropranolol and 7-Nitropropranolol - Sparaco, Rosa; Scognamiglio, Antonia; Corvino, Angela; Caliendo, Giuseppe; Fiorino, Ferdinando; Magli, Elisa; Perissutti, Elisa; Santagada, Vincenzo; Severino, Beatrice; Luciano, Paolo; Casertano, Marcello; Aiello, Anna; et al. (Molecules (Basel, Switzerland), 2022)
We recently identified 6-nitrodopamine and other nitro-catecholamines (6-nitrodopa, 6-nitroadrenaline), indicating that the endothelium has the ability to nitrate the classical catecholamines (dopamine, noradrenaline, and adrenaline). In order to investigate whether drugs could be subject to the same nitration process, we synthesized 4-nitro- and 7-nitropropranolol as probes to evaluate the possible nitration of the propranolol by the endothelium. The separation of the enantiomers in very high yields and excellent enantiopurity was achieved by chiral HPLC. Finally, we used Riguera’s method to determine the absolute configuration of the enantiomers, through double derivatization with MPA and NMR studies.